Oral Corrective Feedback in EFL Classroom (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Feedback is the most essential part in EFL (English as Foreign Language) teaching and learning process. At this stage, students speaking is evaluated so that they know the progress of their learning. This study is aimed at examining the application of teachers’ corrective feedback in classroom interactions. The research used qualitative methods and it used observation sheets and audio recorders. The writer collected data through observations to generate the main data and through interviews to support the primary data. The sample for this study consisted of 34 students and two English teachers. Data were analyzed by a qualitative procedure based on the Mile and Huberman (2013) model. This includes data reduction, data display, and inference. Results showed that the most common corrective feedback used by teachers in classroom interactions was recast, occurring 66.7% or 64 times in the class. Interviews revealed that there were three reasons for using corrective feedback are to help students avoid mistakes; to improve students' grammar, vocabulary, and pronunciation; and to motivate students to learn English better